Contribuição da literatura infanto-juvenil na construção da educação antirracista: uma leitura da obra Amoras, de Emicida - (:unkn) unknown (Universidade Federal do Pampa, 2021)
This work aims to discuss the book “Amoras” (2018). The reflection of this work of children's literature is based on themes from our reality such as blackness, inequality, racism and discrimination. Therefore, tries to contribute to the dissemination of children's literature by black authorship at school, for the formation of readers and for the construction of an anti-racist education.
Contribution of children's literature to the construction of anti-racist education: a reading of Amoras, by Emicida
Keywords: Literatura infantil; Racismo; Educação antirracista; Children's literature; Anti-racist education; CNPQ::LINGUISTICA, LETRAS E ARTES